Strangulating bowel obstruction due to a small intestinal knot in a case of parastomal hernia - Kato, Tetsuro; Miyake, Hideo; Nagai, Hidemasa; Yuasa, Norihiro (Nagoya journal of medical science, 2021)
An intestinal knot is a rare cause of intestinal obstruction. We report a rare case of strangulating bowel obstruction due to a small intestinal knot. A 69-year-old man who had an end colostomy was admitted with severe abdominal pain and vomiting. Contrast enhancement computed tomography showed dilated intestinal loops with decreased contrast enhancement in the parastomal hernia sac. Emergent laparotomy revealed a dilated and congested intestinal loop strangulated by a small intestinal knot. The knot was carefully untied, and the color of the intestinal loop improved subsequently. Intestinal resection was not performed. Immediate diagnosis and prompt surgical treatment are crucial for strangulating small bowel obstruction due to an intestinal knot. A high degree of clinical suspicion of an intestinal knot is needed in patients with a large extra-abdominal cavity.